An analysis of influencing factors on municipal solid waste source-separated collection behavior in Guilin, China by Using the Theory of Planned Behavior. (February 2018) - Ma, Jing; Hipel, Keith W.; Hanson, Mark L.; Cai, Xiang; Liu, Yang
Highlights: Influencing factors on public behavior in MSW separated collection are analyzed. The analyses are based on the extended version of the Theory of Planned Behavior. Attitude and situational factors are major predictors of public behavioral intention. Perceived behavioral control and intention are major predictors of public behavior. Suggestions to decision makers on promoting public behavior are proposed. Abstract: Municipal solid waste (MSW) separation at the source is a key determinant in the success of the whole MSW management process in industrializing countries, especially in China. Implementing MSW source-separated collection heavily depends on the participation of householders, which motivates a thorough understanding of major influencing factors. In this paper, an extended Theory of Planned Behavior (TPB) model was exploited to analyze how householders' attitudes, subjective norms, perceived behavioral control, and situational factors affected their overall behavior. The approach was applied to a case study in Guilin, Guangxi Zhuang Autonomous Region, China, which is representative of wide areas located in-land with a GDP around the national average. After obtaining 848 valid questionnaire responses in the city, a path analysis was executed. The findings suggest that individuals' attitude and situational factors are major predictors of their behavioral intention, while perceived behavioral control and intention play an important role in predicting MSW source-separated collection behavior. The implications of these findings on designing communication campaigns and improving waste management programs were also discussed.